Convincing investors: A study of personal, adapted storytelling and strategic behavior in entrepreneurial fundraising - Pauline Tilla Rittstieg (Junior Management Science (JUMS), 2022)
This inductive study explores the process, through which legitimacy is established for financial resource acquisition, by analyzing the accounts of 15 entrepreneurs on their storytelling and fundraising strategies. The findings show that consistent personal storytelling, venture story adaptation, and strategic behavior increase a venture's chances of receiving financial investments. Taking an entrepreneur-centric perspective in analyzing the practical implementation of cultural entrepreneurship theory, the findings have strong theoretical implications. They suggest extending the model of cultural entrepreneurship to include entrepreneurs' behavior throughout the resource acquisition process. They further contradict the theory that a venture's legitimacy only depends on its existing resources, suggesting that it is also based on the venture's founder's storytelling skills and behavior. As for practical implications, the findings show that investment decisions are not purely fact-based but influenced by investors' emotional involvement and the hype around the venture among investors, which are both a consequence of skillful storytelling and strategic behavior. The study illustrates several effective storytelling and fundraising strategies, providing practical examples for each.
Keywords: 650; Venture legitimacy; Fundraising; Fundraising strategy; Storytelling; Cultural entrepreneurship